Factors influencing CD4+ T cell counts in people living with HIV with end-stage kidney disease - Pretorius, Melanie (My University, 2020)
Introduction: In South Africa, it is estimated that ~7 million people are living with Human Immunodeficiency Virus (HIV). HIV is associated with an increased risk of kidney disease. For people living with HIV (PLWH) who develop end-stage kidney disease (ESKD), access to renal replacement therapy can be difficult. Kidney transplantation is a cost-effective option, with improved overall survival and better quality of life. Eligibility criteria for kidney transplantation in Johannesburg includes a sustained CD4+ T cell count of >200 cells/μl and suppressed HIV replication. This study aimed to investigate the influence of hemodialysis on the lymphocyte subsets in PLWH with ESKD. Methods: Study participants and controls were recruited from renal dialysis centres in Johannesburg. Demographic data, social data, serial CD4+ T cell counts, serial HIV viral load measurements and blood samples were collected (before and after a haemodialysis session). Lymphocyte subsets were then measured. Results: Our cohort showed a statistically significant increase in the post-dialysis % of CD4+ T cells and the absolute CD4+ T cell counts. The longitudinal trend analysis for the % of CD4+ T cells revealed a significant increase in five participants and a single patient had a significant decrease in the longitudinal trend analysis for the absolute CD4+ T cell counts. The longitudinal trend analysis for HIV viral load revealed the majority of our participants were not virologically suppressed. Conclusion: This study showed that haemodialysis does not negatively impact CD4+ T cell count, suggesting that immunologic recovery is not impeded by treatment of the underlying ESKD.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Medicine (Haematology) to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020